Experimental and numerical investigations on the thermal performance of a modified evacuated tube solar collector: Effect of the bypass tube. (1st May 2019) - Jowzi, Mohammad; Veysi, Farzad; Sadeghi, Gholamabbas
Highlights: The thermal performance of the modified evacuated tube solar collector was experimentally investigated using the bypass tube. The modified solar water heater was simulated by CFD analysis considering the real amount of solar radiation during the day. The optimum diameter of the bypass pipe was numerically obtained. The solar radiation on the collector surface was experimentally measured. Abstract: Many factors impact the thermal efficiency of the evacuated tube solar collectors (ETSCs) and numerous studies have been carried out to increase the efficiency of ETSCs. In this study, the stagnant region at the bottom of the evacuated tube has been removed using a bypass tube to connect the storage tank to the bottom of the modified evacuated tube. The thermal performance of a modified evacuated tube solar collector (METSC) has been investigated experimentally and numerically. The thermal characteristics of the METSC were compared to those of a commercial sample under equal environmental conditions. Furthermore, the impact of the diameter of the bypass pipe on the velocity profile, and temperature distribution of the fluid inside the modified collector has been investigated numerically to achieve the optimum diameter. The results demonstrate that this structure modification improves the collector performance due to removing the stagnant region at the bottom of the evacuated tube and the storage tank. This modification made the temperature distribution inside the pipe and tank more uniform, and increased the efficiency up to 11%. Moreover, useful gain of the solar collector in the modified model was 25% more than that of the typical model over a one-hour period. In addition, for the same duration, the average temperature of water inside the tank enhanced by 1.5 °C in the METSC in comparison to the typical model under equal environmental conditions.